EVALUATION OF DRAINAGE CHANNEL AGAINST FLOOD EVENTS IN KUNINGAN AREA, SOUTH JAKARTA - Ridwan, Muhammad
DKI Jakarta experienced several times the flood event was quite large, especially after changes in land use that were increasingly massive from year to year. One of the major flood events that occurred was in early 2020, where one of the flood concentration points was in Kuningan, Setiabudi, South Jakarta. This is not good considering Setiabudi as an area of the golden triangle of the economy in DKI Jakarta, so that the flood events that occur in this area will be enough to disrupt the economic rate of DKI Jakarta as a province. Drainage studies are carried out by taking 3 villages as a study, namely Setiabudi, Karet, and Karet Kuningan Village. The drainage channel used is a PHB drainage channel. The output from the drainage system at the study site is flowing to Krukut River, Cideng River, and West Setiabudi Reservoir. The area of the study drainage area is 285.55 ha. Influential rain stations are Cawang and Kemayoran Rain Stations. The data series used is for 15 years (2004-2018). The rainfall criteria of the plan used are with a 10-year and 25-year return period as control. Based on the results of SWMM modeling, drainage models with a 10-year return period do not produce flood overflows on all drainage channels while for drainage models with a 25-year return period produces flood overflows on several nodes with a total flood volume of 10,727 m3. Then, drainage at the study site (Setiabudi) is still able to master drainage discharge with a limit of 232 mm of draft rainfall application. When the value above 232 mm is applied, there is an overflowing drainage channel in one or more of the drainage channels at the study site. An alternative possible solution to the problem of flooding at the study drainage site is the application of catchment wells, considering the allocation of land around the study site based on DKI Jakarta Regional Regulation No. 1 of 2012 concerning RTRW 2030, namely for settlements and offices. It takes at least 60 catchment wells in Setiabudi Village and 77 catchment wells in Karet Kuningan Village. Furthermore, the maximum flood discharge in the 100-year return period using the SCS method in Krukut River amounted to 233.47 m3 / sec. The 100-year return period is determined based on design criteria for rivers in the nation's capital, which is taken from the reference of The Ministry of Public Works and Public Housing Regulation No. 28 of 2015 concerning the Determination of River Border Lines and Lake Border Lines. With an alternative solution in the form of the application of levees, the flood puddle area which previously amounted to 1.37 ha dropped significantly to 0.31 ha, with a decrease rate of 77.4%. Then, the application of a comparison of land use conditions in 1990 and 2012 resulted in a difference in flow conditions that were not too significant, where the difference in flood inundation area by 21.9% (in 1990 by 1.07 ha and in 2012 by 1.37 ha). Then, the maximum flood discharge in the 100-year return period using the rational method in Cideng River amounted to 353 m3 / sec. Based on the best Cideng River cross-sectional analysis, obtained channel width of 22 m and total height (H) plus freeboard of 11.35 m. The drainage outlet that flows to Cideng River should at least have an elevation above 15 mdpl. Furthermore, based on an analysis of The West Setiabudi Reservoir, it shows that there is no need for operating patterns from the reservoir to remove water from the reservoir (Vout is not yet needed) with the reservoir capacity (271,654.3 m3) still much larger than the incoming drainage discharge (75.17 m3). Therefore, flood events in J10 and J40 can be anticipated by making modifications to the slope of both drainage channels.